Seasonal and interannual variability of fast ice extent in the southeastern Laptev Sea between 1999 and 2013. Issue 12 (12th December 2015) - Selyuzhenok, V.; Krumpen, T.; Mahoney, A.; Janout, M.; Gerdes, R.
Abstract: Along with changes in sea ice extent, thickness, and drift speed, Arctic sea ice regime is characterized by a decrease of fast ice season and reduction of fast ice extent. The most extensive fast ice cover in the Arctic develops in the southeastern Laptev Sea. Using weekly operational sea ice charts produced by Arctic and Antarctic Research Institute (AARI, Russia) from 1999 to 2013, we identified five main key events that characterize the annual evolution of fast ice in the southeastern Laptev Sea. Linking the occurrence of the key events with the atmospheric forcing, bathymetry, freezeup, and melt onset, we examined the processes driving annual fast ice cycle. The analysis revealed that fast ice in the region is sensitive to thermodynamic processes throughout a season, while the wind has a strong influence only on the first stages of fast ice development. The maximal fast ice extent is closely linked to the bathymetry and local topography and is primarily defined by the location of shoals, where fast ice is likely grounded. The annual fast ice cycle shows significant changes over the period of investigation, with tendencies toward later fast ice formation and earlier breakup. These tendencies result in an overall decrease of the fast ice season by 2.8 d/yr, which is significantly higher than previously reported trends. Key Points: Annual fast ice cycle in the southeastern Laptev Sea is characterized The main factors controlling annual fast ice cycle are revealed The trends in timing of the annual cycle are estimated